A novel application of terpene compound α-pinene for alternative use of sulfur dioxide-free white wine. Issue 1 (1st January 2020) - Shih, Ming-Kuei; Lai, Yu-Heng; Lin, Chia-Min; Chen, Yu-Wei; Hou, Zheng-Ting; Hou, Chih-Yao
ABSTRACT: Sulfur dioxide is widely used as a preservative in winemaking owing to its antioxidant and antimicrobial properties. However, it exerts adverse effects on health, causing dermatitis, urticaria, angioedema, diarrhea, and abdominal pain. In the present study, we used α-pinene, which is a fragrant monomeric compound derived from fruit-aroma compounds, as an alternative for SO2 in white wine fermentation. Three concentrations of α-pinene, 0.03125 g/100 mL, 0.0625 g/100 mL, and 0.125 g/100 mL were used. White wine added with SO2 at 40 ppm was also used (SO2 group). The white wine without addition of SO2 and α-pinene as used as the control. Total bacterial count and physicochemical characteristics including pectin content, degree of esterification, ethanol content, color, total phenolic acid content, and DPPH activity were analyzed. The antibacterial activities of α-pinene groups were similar to SO2 group but significantly higher than the control group. Specifically, 0.03125 g/100 mL and 0.0625 g/100 mL α-pinene groups showed significantly higher transmittance, L values, and color values than the control at the day 180, which suggested that the addition of α-pinene effectively inhibited the browning of white wine during storage. These findings indicated that α-pinene possessed an excellent antibacterial ability and could be a viable alternative for SO2 in winemaking.